Genetic implications in patients with NAFLD - Misiak, Jakub; Kępczyk, Martyna; Kwaśniewska, Oliwia; Urbaś, Michał; Ojdana, Miłosz; Demianenko, Yehor; Czekaj, Oliwia; Kościołek, Aleksandra; Kościołek, Dawid; Surowiecka, Kaja (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Non-alcoholic fatty liver disease’s growing prevalence and the complications it brings constitutes a serious problem nowadays. According to this, better understanding of mechanisms laying on the ground of its pathogenesis is a crucial factor to better understand this disease and develop interventions to counter its effects. Genetic relationships with NAFLD are known and they show great variation of mechanisms underlying their impact on subjects’ metabolic state. Due to this fact the assumption that it is worth collecting these connections in one place was made, so that it is easier to navigate in them. Mostly studies refer to rodents trials, we focused on studies referred to people with NAFLD diagnosis. Material and method: The literature was scrutinised in the Google Scholar database, in the Pubmed database with the use of following keywords: “genetics”, “genes”, “non-alcoholic fatty liver disease”, “NAFLD”, “non-alcoholic steatohepatitis”, “NASH”. Results: NAFLD as a metabolic disease has many links with metabolic pathways encoded by various genes. When it comes to genetic factors, we can specify gene expression single nucleotide polymorphisms (SNP) and genes methylation. All of these aspects affect activity of coded proteins and what follows this is its impact on human metabolism. These factors have been studied in the work of other researchers. Conclusions: Non-alcoholic fatty liver disease’s growing prevalence and the complications it brings constitutes a serious problem nowadays. Genetic relationships with NAFLD are known and they show great variation of mechanisms underlying their impact on subjects’ metabolic state.